2001
DOI: 10.1002/ajh.10000
|View full text |Cite
|
Sign up to set email alerts
|

Novel heterozygous missense mutation in the platelet glycoprotein Ibβ gene associated with isolated giant platelet disorder

Abstract: The glycoprotein (GP) Ib/IX/V complex plays an important role in primary hemostasis, serving as the platelet receptor for von Willebrand factor (vWF). Recent studies have shown that the phenotype caused by mutations in the subunits of the GPIb/IX complex spans a wide spectrum; from the normal phenotype, to isolated giant platelet disorders (GPD), and to the full-blown bleeding disorder, the Bernard-Soulier syndrome (BSS). We characterize here a novel missense mutation of the GPIbb gene associated with isolated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 26 publications
1
41
0
Order By: Relevance
“…Several of the GP Ib␤ gene mutations that have been described are missense mutations. 23,[28][29][30] In general, these mutations might be expected to have a minimal effect on transcript stability. However, in the case of Watanabe et al, 8 who observed abnormal vesicles, the mutation is a 13-bp deletion within the signal peptide coding region of the GP Ib␤ gene.…”
Section: Discussionmentioning
confidence: 99%
“…Several of the GP Ib␤ gene mutations that have been described are missense mutations. 23,[28][29][30] In general, these mutations might be expected to have a minimal effect on transcript stability. However, in the case of Watanabe et al, 8 who observed abnormal vesicles, the mutation is a 13-bp deletion within the signal peptide coding region of the GP Ib␤ gene.…”
Section: Discussionmentioning
confidence: 99%
“…The symptomatic patients were homozygotes, because they had a deletion of one chromosome containing the GpIbb gene and a mutation in the other. Furthermore, BSS associated with the defective beta subunit of GpIb (BSS type B) has been reported in 22q11.2-deleted patients [4][5][6] and in homozygotes and heterozygotes for missense or non-sense mutations in GPIbb [8][9][10][11][12].…”
Section: R P a L L O T T A * V E V A N G E L I S T A M M A mentioning
confidence: 99%
“…Interestingly, microdeletions within chromosome 22q11 which result in the loss of one GPIBB allele (velocardiofacial syndrome) reduce the surface expression of GPIb/IX/V by 50%; however, in most cases, these mutations do not induce thrombocytopenia or platelet macrocytosis. 19 Thus, 50% expression of the GPIb/IX/V complex appears to be sufficient for 20 result in the production of larger platelets. Not enough data are presently available to unravel the molecular mechanisms that underlie these differences, and further studies on the transcription and translation of mutated genes, as well as on the processes that regulate the assembly of the GPIb/IX/V complex, are required to fully understand the pathogenesis of BSS.…”
mentioning
confidence: 99%